Towards a plan of actions for mankind : long-range energetic resources and growth, v.2: proceedings of the world conference, Paris, 9-13 September 1974 - Marois, M.; Institut de la vie. (London : New York : Pergamon Press, 1977)
Articles prepared for the world conference sponsored by the Institut de la vie.
Proceedings of the world conference sponsored by Institut de la vie and held in Paris, Sept. 9-13, 1974.
Includes bibliographical references.
lje 24/01/2018
Loans
Keywords: Power resources; Environmental protection; Environmental policy; Human ecology